A new class of deep-blue emitting Cu(i) compounds – effects of counter ions on the emission behavior. Issue 46 (3rd November 2015) - Gneuß, Timo; Leitl, Markus J.; Finger, Lars H.; Yersin, Hartmut; Sundermeyer, Jörg
Abstract : A series of three deep-blue emitting Cu(i ) compounds with a tripodal ligand is investigated. The compounds only deviate by their respective counter anions. These anions have a significant impact on the emission behavior. Abstract : Three deep blue emitting Cu(i ) compounds, [Cu(PPh3 )tpym]PF6, [Cu(PPh3 )tpym]BF4, and [Cu(PPh3 )tpym]BPh4 (tpym = tris(2-pyridyl)methane, PPh3 = triphenylphosphine) featuring the tripodally coordinating tpym and the monodentate PPh3 ligands were studied with regard to their structural and photophysical properties. The compounds only differ in their respective counter ions which have a strong impact on the emission properties of the powder samples. For example, the emission quantum yield can be significantly increased for the neat material from less than 10% to more than 40% by exchanging BPh4 − with PF6 − . These effects can be linked to different molecular packings which depend on the counter ion. In agreement with these results, it was found that the emission properties also strongly depend on the surrounding matrix environment which was elucidated by investigating photophysical properties of the compounds as powders, doped into a polymer matrix, and dissolved in a fluid solution, respectively. The observed differences in the emission behavior can be explained by different and pronounced distortions that occur in the excited state. These distortions are also displayed by density functional theory (DFT) calculations.